Plant-based coagulants for halal cheese production - Rahma, Amiroh Auliya; Issustiarani, Azzahra (Halal Studies and Society, 2025)
Advancements in cheese-making technology have successfully integrated traditional methods with contemporary innovations, enhancing efficiency, sustainability, and product quality. Traditional cheese production typically uses animal rennet, which is sourced from the stomachs of young ruminants. This rennet contains the enzymes chymosin and pepsin, which are essential for the milk coagulation process in cheese making. Due to the limited availability of animal rennet and the rising demand for cheese and halal food products, the market has expanded beyond Muslim consumers to include non-Muslim individuals, leading to the exploration of alternative plant-based coagulants. Therefore, this study aims to evaluate the potential use of plant-based coagulants in producing halal cheese while identifying the challenges associated with the production process. These challenges include proteolytic activity, which can lead to a bitter taste, and inconsistencies in coagulant quality due to variations in the sources of the plants. The current study focuses on different types of plant proteases, such as aspartate, cysteine, and serine, extracted from different parts, as well as protease production techniques. It also explores coagulant quality parameters, such as milk clotting activity, proteolytic activity, optimal temperature, and pH, as well as their effects on the physicochemical and organoleptic properties of cheese. The results are expected to provide comprehensive scientific insights for the development of effective alternative coagulants to meet the needs of the halal cheese market in the future.